Accession management: Combining or splitting accession as a tool to improve germplasm management efficiency - Sackville-Hamilton, N. Ruaraidh; Engels, J.M.M.; Hintum, T.J.L. van; Koo, B.; Smale, Melinda; International Plant Genetic Resources Institute (2002)
The publication is aimed at curators and other genebank staff. It is meant to be a discussion guide, to provide ideas and suggestions on how management procedures can be improved, and to point to possible implications of a given management procedure. It does not aim to provide a definitive theory on composing genebank collections or on the management of accessions, nor does it attempt to provide a complete overview of possible approaches and procedures. The reader is invited to give feedback to IPGRI (comments, additions, alternative approaches, etc.) on any aspect of the contents, and thus contribute to the discussion started with this publication.